Beer with Probiotics: Benefits and Challenges of Their Incorporation - Diana Santos; Luisa Barreiros; Ângelo Jesus; Ana Luísa Silva; João Paulo Martins; Ana Isabel Oliveira; Cláudia Pinho (Beverages)
Beer is considered one of the most consumed beverages worldwide and a potential vehicle for probiotics. However, there are several technical challenges to overcome during the production and storage of beers, as probiotics must remain viable until the moment of consumption. Therefore, this work aims to discuss how the incorporation of probiotics improves or adds value to beer and which variables influence the viability of the process. This is a narrative review of the literature with research in the PubMed, Web of Science, and b-on databases for articles related to the incorporation of probiotics in beer and the variables that influence the process. The results demonstrated that the incorporation of probiotics into beer faces technical challenges such as probiotic selection, pH, the presence of alcohol, and beer’s production and storage temperatures. However, strategies such as immobilizing probiotics in alginate, alginate–silica, and durian husk powder, fermentation with the yeast Saccharomyces cerevisiae var. boulardii, and co-fermentation with probiotics permit us to overcome these barriers. Thus, incorporating probiotics into beer brings added value, potentially increasing antioxidant activity and phenolic compound content and providing unique flavors and aromas. Nevertheless, strict control of the technical conditions involved is necessary to ensure probiotic viability and the health benefits they confer.